Yusuf Akçura’nın TBMM’deki faaliyetleri (1923-1935) - Demir, Gafar (My University, 2008)
Rusya’dan gelen Türk aydınlarından olan Yusuf Akçura; Türkiye’nin kültür ve düşünce hayatına çok önemli etkileri olmuştur. Bu isim Osmanlının son dönemi ve Cumhuriyetin ilk yıllarındaki millileştirme çalışmalarının öncülerinden olmuştur. İktisat ve tarihin milli olmasını savunmuş ve Milli Tarih oluşturma çabalarında birinci derecede rol oynamıştır. Eserimizde Yusuf Akçura’nın hayatı, eserleri ve 1918’de Hilâl-i Ahmer temsilcisi olarak Rusya’daki Türk esirlerini kurtarmak maksadıyla yurt dışında yürüttüğü faaliyetlerin yanı sıra ağırlıklı olarak 1923 Ağustos’undan 11 Mart 1935’te ölümüne kadar Türkiye Büyük Millet Meclisi’nde milletvekili sıfatıyla yaptığı çalışmalar incelenecektir. Eserimizin başlıca kaynağı Türkiye Büyük Millet Meclisi Zabıt Cerideleri’dir. İstanbul’daki bütün üniversiteler gezilerek, bugüne kadar yayınlanmış bulunan bütün TBMM Zabıt Cerideleri sabırla ve titizlikle incelenmiş; Milletvekili olduğu dönemlerdeki Yusuf Akçura’nın TBMM’deki faaliyetleri ele alınmıştır.

Russia origined Turkish philosopher Yusuf Akçura, had a strong and important influence upon Turkish culture and philosophy. His name became a pioneer of the operation to nationalize in the last period of the Ottoman Empire and the very first periods of the Commonwealth. He maintained that the economy and history are to be known as national subject, also he took the highest part at the application to generate the National History. In our work, besides his life, his achievements and progress he as standing for Hilal-i Ahmer, had made to rescue Turkish thralls in Russia in 1918, rather his studies prepared at the national congress as a congressman will be analyzed starting from august of 1923 and up to his death in march of 1935. The main source of our work is the officially recorded newspapers registers of the Ottoman grand assembly which are belong to the great national congress of Türkiye. During preparing the workout all universities in İstanbul were visited, all officially recorded newspapers registers of the Ottoman grand assembly published were examined exactly, and all activities he had made in the great congress as a congressman were approached.
Keywords: Tarih; TBMM (Türkiye Büyük Millet Meclisi)